(untitled) (International Journal of Ayurveda and Pharma Research, 2018)
Azhinjiathikashayam is a herbo mineral Siddha poly herbal formulation said for the management of Madhumegam (Type-2 Diabetes mellitus) in ancient Siddha literature. The study drug was subjected to estimate the therapeutic efficacy in Madhumegam patients. A well designed study protocol was approve by Institutional Ethics Committee and the clinical study was conducted as an open clinical trial in OPD/IPD of Ayothidoss pandithar Hospital of National Institute of Siddha Chennai. Based on the inclusion criteria 40 Madhumegam patients (Type -2 Diabetes mellitus) were enrolled in this study. Informed consent was obtained from each patient before study initiation. 60ml of Azhinjiathikashayam was administered orally before food twice a day for a period of 90 days and advised to follow the prescribed dietary regimen. All the baseline data, Laboratory investigations were recorded in the prescribed Case Report Form of each patient. Blood sugar level in fasting and postprandial was done once in 30 days and HbA1c was done before treatment (0th day) and after treatment (90th day). The clinical assessment was recorded once in 10 days. Paired t test was used to test the significance of treatment using before and after treatment data on HbA1c, Clinical symptoms, Blood sugar fasting and postprandial. The level of significance probability 0.05 was used to test the treatment difference and the values are statistically significant. In this study there is statistically significant difference between before and after treatment on average HbA1c, average blood sugar of fasting and average clinical feature score (p < 0.0001).